« Et le bronzage de tes fesses dessine un coeur » - Réflexions sur les expériences lesbiennes des plages - Rachele Borghi (L'Espace Politique)
This paper builds on the literature in social sciences (in particular in geography) regarding the gays' visibility and processes of territorialization in relation to coastal recreative space (beaches), to focus on the experience of those who identify themselves as lesbian. It questions the lesbian sexual and gender identity in relation to space and in particular to the access to the public space, focusing on the analysis of the link between sexual and gender norms, in relation to leisure practices. The interviews indicated the internalization of the practices and behaviors that are typical of women's experience of public space. The lesbians interviewed declare not to consider the beach as a safe space. Although the lesbian experience of the beach is influenced by the internalization of gender norms, the weight of socialization can be counterbalanced by the political positioning of each person. The paper shows that the lesbians' experience of the beach involves specific issues that are linked to their belonging to a minority group, not only in quantitative but also in political terms : the lesbians' experience of the beach brings back to the social construction of their sexuality.